High School Teachers’ and Students’ Perception of ICT Use in Learning English - Siti Rejeki (Stairs, 2021)
This study was conducted to find out high school teachers' and students’ perceptions of the use of digital technology, commonly called Information and Communication Technology (ICT), in teaching and learning English. The research used a qualitative method with quantitative data collected from a questionnaire and interviews with high school English teachers and students at MGMP Jakarta Timur I. The results showed that both respondents perceive positive attitudes towards the potentials and benefits of ICT use in English teaching and learning activities. However, their mastery of ICT competencies is high, especially in the Basic Computer and Internet Basic competencies, but insufficient in ICT competencies for learning and Advanced Computer Competence. Even so, the teachers think that they need more training whereas the students do not think the same. This result can be used as evaluation for English teachers as implementers in the field and for institutions as policy makers.